2010
DOI: 10.1242/jeb.037663
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and avian infectious diseases

Abstract: SummaryIn this time of unprecedented global change, infectious diseases will impact humans and wildlife in novel and unknown ways. Climate change, the introduction of invasive species, urbanization, agricultural practices and the loss of biodiversity have all been implicated in increasing the spread of infectious pathogens. In many regards, deforestation supersedes these other global events in terms of its immediate potential global effects in both tropical and temperate regions. The effects of deforestation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 97 publications
(99 reference statements)
3
80
3
4
Order By: Relevance
“…Similar results have been demonstrated for avian malaria, with deforestation producing variable prevalence patterns at both local and regional scales (see Sehgal 2010, LaPointe et al 2012). For example, recent studies in Africa by Bonneaud et al (2009) and Loiseau et al (2010) found higher Plasmodium prevalence in birds inhabiting pristine forests, whereas Chasar et al (2009) revealed one parasite species was more abundant in disturbed sites and another more so in pristine sites.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results have been demonstrated for avian malaria, with deforestation producing variable prevalence patterns at both local and regional scales (see Sehgal 2010, LaPointe et al 2012). For example, recent studies in Africa by Bonneaud et al (2009) and Loiseau et al (2010) found higher Plasmodium prevalence in birds inhabiting pristine forests, whereas Chasar et al (2009) revealed one parasite species was more abundant in disturbed sites and another more so in pristine sites.…”
Section: Introductionsupporting
confidence: 80%
“…), primarily through their effect on vector species (Patz et al 2000;Harvell et al 2002). In many parts of the world, deforestation for agricultural development is a common anthropogenic driver of changes in parasite transmission rates (Yasuoka and Levins 2007;Sehgal 2010;LaPointe et al 2012). Studies of human malaria in Asia, Africa and the Amazon region have shown that forest fragmentation and increasing edge habitat produce complex host-vector responses; these can either increase or decrease malaria prevalence depending on subsequent land use and the breeding ecology of local vector species (see Yasuoka andLevins 2007, Stefani et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation is associated with loss of biodiversity, the alteration of many fundamental aspects of ecosystems, and an increase in the prevalence and incidence of many human vector-borne diseases 25 . The year-round high rainfall and temperatures in tropical forests are ecological characteristics that favor the development of many kinds of mosquitoes that transmit pathogens that cause disease in humans 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Forest logging directly or indirectly reduced the habitat suitability of forest fauna (Potts, 2011) such as butterflies and mammals (Brook et al, 2003;Sehgal, 2010) and monkeys (Collins, 2008). Due to logging, the forest becomes fragmented, more irregular and isolated (Echeverria et al, 2007) which affects on distribution, richness and diversity of avian species (McCarthy, 2012).…”
Section: Introductionmentioning
confidence: 99%